The Influence of Brand Ambassador and Social Media Marketing on Purchase Intention Through Brand Image (Study on Consumers " Sang Dewa Snack") - Valma Putri Sabella; Agus Hermawan; Titis Shinta Dhewi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Brand ambassadors and social media marketing are effective marketing strategies in promotions to encourage purchases. This study aims to determine the direct and indirect effect of brand ambassadors and social media marketing on purchase intention through the brand image of Sang Dewa consumers. This study uses a descriptive explanatory quantitative approach. The population of this research is prospective consumers of Sang Dewa, the sampling technique used purposive sampling totaling 198 respondents. Data analysis of this research was carried out using the SEM Partial Least Square (PLS) method using WarpPLS 7.0 software, descriptive analysis and Sobel test. The results show that: 1) brand ambassadors have a positive and significant direct effect on brand image & purchase intention 2) social media marketing has a direct positive and significant effect on brand image & purchase intention 3) brand image has a direct positive and significant effect on purchase intention 4) brand ambassador has a positive and significant effect on purchase intention through brand image 5) social media marketing has a positive and significant effect on purchase intention through brand image. Based on the results of this study, the researcher provides suggestions, namely adjusting product characteristics with brand ambassador figures and carrying out more effective promotional activities.